2019
DOI: 10.12788/jhm.3328
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Progress Note: High Flow Nasal Cannula Therapy for Bronchiolitis Outside the ICU in Infants

Abstract: Viral bronchiolitis is the most common indication for infant hospitalization in the United States.1 The treatment mainstay remains supportive care, including supplemental oxygen when indicated.1 High flow nasal cannula (HFNC) therapy delivers humidified, heated air blended with oxygen, allowing much higher flow rates than standard nasal cannula therapy and is being used more frequently in inpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Through the nasal cannula, it provides a heated, humidi ed air-oxygen combination [2], [3]. The majority of the HFNC studies include respiratory infections such as bronchiolitis and pneumonia, especially in pediatric wards and emergency departments where it is used as rst-line treatment [4], [5]. Nasal high-ow provides some positive airway pressure and reduces the effort of breathing [6], [7] and the use of HFNC found to be well tolerated by children [8].…”
Section: Introductionmentioning
confidence: 99%
“…Through the nasal cannula, it provides a heated, humidi ed air-oxygen combination [2], [3]. The majority of the HFNC studies include respiratory infections such as bronchiolitis and pneumonia, especially in pediatric wards and emergency departments where it is used as rst-line treatment [4], [5]. Nasal high-ow provides some positive airway pressure and reduces the effort of breathing [6], [7] and the use of HFNC found to be well tolerated by children [8].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Additionally, little medical evidence exists to guide the weaning of supplemental oxygen, leading to significant variability in clinical care. [18][19][20] This is further complicated by subjective evaluation of patients with bronchiolitis due to rapidly changing physical examination findings and poor validity of measurement instruments such as respiratory distress index. 21 The combination of limited evidence-based interventions, subjective evaluation, and no established standard of care for de-escalation of support contributes to overtreatment and increased resource utilization in the care of patients with bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%
“…16 These data suggest that HFNC has become over-utilized in some patients who will not benefit from it, likely due to a lack of clear criteria for initiation of HFNC. 17,18 Additionally, little medical evidence exists to guide the weaning of supplemental oxygen, leading to significant variability in clinical care. [18][19][20] This is further complicated by subjective evaluation of patients with bronchiolitis due to rapidly changing physical examination findings and poor validity of measurement instruments such as respiratory distress index.…”
Section: Introductionmentioning
confidence: 99%
“…A s an appealing, physiologically plausible treatment, humidified oxygen delivery via high-flow nasal cannula (HFNC) has been rapidly adopted for the treatment of bronchiolitis despite weak evidence supporting its routine and early use in hypoxemic infants. 1 Although HFNC use has been associated with decreased work of breathing and lower rates of progression to invasive ventilation in some studies, the one large trial published on the topic found no difference between early HFNC and standard oxygen therapy on length of stay in hospital, duration of oxygen therapy, or rates of intubation. 2,3 No adequately powered studies have examined the effect of ward-based HFNC initiation on ICU transfer, an outcome that it is designed to prevent.…”
mentioning
confidence: 99%